PERFORMANCE OF SPRINKLER AND DRIP IRRIGATION IN CULTIVATION OF CRYSTAL GUAVA (Psidium guajava L.) AT P.T. GGPPG 4 EAST LAMPUNG - Suprapto Suprapto; Muhammad Idrus; I Gde (Jurnal Penelitian Pertanian Terapan, 2024)
This research was conducted at PT Great Giant Pineapple Plantation Group 4 (GGPPG4), located in Rajabasa Lama, East Lampung, to evaluate the effectiveness of two irrigation systems in the cultivation of crystal guava (Psidium guajava L. cv. Kristal). The mini sprinkler irrigation system was applied in Block 408 P (4.2 ha) and the drip irrigation system in Block 412 N (3.46 ha). Parameters evaluated included water uniformity coefficient, soil moisture condition, water usage efficiency, and water productivity. The results showed that the water uniformity coefficient of the mini sprinkler irrigation system reached 88.49% (classified as good), higher than the drip irrigation system, which was 77.20% (classified as fair). However, drip irrigation was more efficient in water usage with a total requirement of 2,516 m³/ha, compared to 3,260 m³/ha for the mini sprinkler system. The water productivity of drip irrigation reached 11,942 kg/m³, much higher than the mini sprinkler system, which only reached 4,965 kg/m³. Although the mini sprinkler system had better water distribution uniformity, the efficiency and water productivity of drip irrigation provided more optimal results. This study indicates that drip irrigation is superior in supporting efficient and sustainable crystal guava cultivation at the research site.